2022
DOI: 10.3390/ijerph20010605
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pregnancy: A Systematic Review of Adolescent Pregnancy in Ghana, Liberia, and Nigeria

Abstract: There is a high incidence of adolescent pregnancy in West Africa. The objective of this study is to highlight the health impacts of adolescent pregnancy through a systematic review. A search was conducted in the electronic databases of Google, Google Scholar, SCOPUS, EBSCO, CINAHL, Web of Science, African Journals Online (AJOL), and the Demographic Health Surveys (DHS) Program. The study found anemia, complications of pregnancy, obstetric and gynecological risks, unsafe abortions, and psychological effects to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…17 A systematic review conducted to identify the adolescent maternal health impacts of pregnancy in Ghana, Nigeria and Liberia shows a high prevalence of anaemia, postpartum haemorrhage, cephalopelvic disproportion, hypertensive disorders and unsafe abortion in addition to psychological effects which adversely affect pregnancy outcome in this age group. 18 The burden of maternal mortality among adolescents is much higher in developing countries of sub-Saharan Africa and Asia. 15 The weak health systems in most developing countries further increase their risk of dying from pregnancy complications when it occurs.…”
Section: Discussionmentioning
confidence: 99%
“…17 A systematic review conducted to identify the adolescent maternal health impacts of pregnancy in Ghana, Nigeria and Liberia shows a high prevalence of anaemia, postpartum haemorrhage, cephalopelvic disproportion, hypertensive disorders and unsafe abortion in addition to psychological effects which adversely affect pregnancy outcome in this age group. 18 The burden of maternal mortality among adolescents is much higher in developing countries of sub-Saharan Africa and Asia. 15 The weak health systems in most developing countries further increase their risk of dying from pregnancy complications when it occurs.…”
Section: Discussionmentioning
confidence: 99%
“…It attempts to build a deep understanding of the topic, get an overview of what is already known in the topic field and discover the gap to be covered by the research. Different consulted documents revealed that teen mothers constitute a major challenge at individual, family and national development (Bah, 2016;Adebola, 2018;Morgan et al 2022;Lambonmung et al, 2022). After being impregnated, a high percentage of teen mothers drop schools and a few of them resume school after delivering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the study by provides a systematic review of the effects of adolescent pregnancy in West African countries, including Nigeria (Lambonmung et al, 2022). This study highlights the adverse health impacts of adolescent pregnancy, such as anemia, complications of pregnancy, unsafe abortions, and psychological effects.…”
Section: Significance Of Laboratory Science In Women's Healthmentioning
confidence: 99%
“…This study highlights the adverse health impacts of adolescent pregnancy, such as anemia, complications of pregnancy, unsafe abortions, and psychological effects. The insights from this study are crucial for developing targeted interventions to prevent pregnancy in young women and mitigate the adverse effects, emphasizing the role of laboratory science in understanding and addressing women's reproductive health issues (Lambonmung et al, 2022).…”
Section: Significance Of Laboratory Science In Women's Healthmentioning
confidence: 99%